Beyond scandal? Blockchain technologies and the fragile legitimacy of post-2008 finance - Malcolm Campbell-Verduyn; Moritz Hütten (Finance and Society, 2019)
How do applications of emergent technologies contribute to the social legitimacy of finance? To address this question, we examine a set of technologies that have received increasing industry, media, and scholarly attention over the past decade: blockchains. Harnessing the concepts of "moral economy" and "scandal", we identify both possibilities and limits for blockchain applications to legitimate a range of monetary and investment activities. However, we also find that a persistent individualisation of responsibility for failures and shortcomings with "live" blockchain experimentation has undermined the potentially legitimating aspects of this technology. Combining a reliance on technological fixes with a persistent individualist moral economy, we conclude, works against efforts to confront head-on the tensions underpinning the on-going legitimacy crises facing finance.
Keywords: 300; Blockchain; cryptocurrency; digital money; technology; legitimacy; scandal